The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.oraloncology.2020.105033
|View full text |Cite
|
Sign up to set email alerts
|

Using 3D-printed nose models in nasopharyngeal swab training

Abstract: Background The COVID-19 pandemic has swept across the globe with massive effects on health care systems as well as global economies. Enhanced testing has been put forward as a means to reduce transmission while awaiting the development of targeted therapy or effective vaccination. However, achieving accurate testing necessitates proper nasopharyngeal swab techniques. Methods and results We aimed to design and investigate the utility of an anatomically accurate three-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…2a . Flexibility is essential for NP swabs as they must bend and penetrate far into the nasopharyngeal cavity to collect sufficient samples 22 , 26 , 31 , 32 . Figure 2b demonstrates that the reactive bending force (platform force) of the microlattice NP swab is up to 7 times less than that of the commercial NP swabs, and the flexibility (the reciprocal of the slope) of the microlattice NP swabs are up to ~11 times of that of the commercial NP swab.…”
Section: Resultsmentioning
confidence: 99%
“…2a . Flexibility is essential for NP swabs as they must bend and penetrate far into the nasopharyngeal cavity to collect sufficient samples 22 , 26 , 31 , 32 . Figure 2b demonstrates that the reactive bending force (platform force) of the microlattice NP swab is up to 7 times less than that of the commercial NP swabs, and the flexibility (the reciprocal of the slope) of the microlattice NP swabs are up to ~11 times of that of the commercial NP swab.…”
Section: Resultsmentioning
confidence: 99%
“…Current advancement in the fields of tissue engineering, material sciences, and additive manufacturing provide the opportunity to augment approaches to reconstruction of head and neck structures. In fact, 3D printing has been applied to surgical training in otolaryngology, an example being the use of 3D printed temporal bones for surgical simulation, [4,97] medical teaching, [98,99] as well as customized surgical planning. [100][101][102][103] Moreover, clinical applications of 3D printing in otolaryngology have included the successful treatment of severe airway malacia using a 3D printed, personalized PCL external airway splint.…”
Section: D-bioprinting Applications In Otolaryngologymentioning
confidence: 99%
“…Literature has demonstrated that the use of three-dimensional (3D) printed models or manikins to train healthcare workers on nasopharyngeal tests was useful and improved both confidence and comfort in performing the tests. [16][17][18] Limited studies have highlighted educational models for teaching specimen collection for infectious diseases in pharmacy education. 2,4,19 McKeirnan and colleagues describe implementation of POCT content for second year pharmacy students as part of a weeklong 2-credit hour required course.…”
Section: Introductionmentioning
confidence: 99%